Two-step catalytic dehydrogenation of formic acid to CO2 via formaldehyde. (15th January 2019) - Viasus, Camilo J.; Alderman, Nicholas P.; Peneau, Virginie; Gabidullin, Bulat; Vidjayacoumar, Balamurugan; Albahily, Khalid; Gambarotta, Sandro
Abstract: Formic acid has been decomposed into hydrogen and carbon dioxide through a two-step process involving the formation of formaldehyde. This allows the formation of carbon dioxide and hydrogen in two different steps, negating the need for gas separation. A novel system for the catalytic disproportionation of formic acid into formaldehyde and carbon dioxide was thus far developed using monoclinic bismuth chromate hydroxide proto-catalyst, m- Bi(OH)CrO4 . The catalytically active species, BiCrO4, was isolated and its activity assessed for thermal disproportionation of formic acid under mild conditions (200–300 °C, tube furnace). A maximum formaldehyde production rate of 0.065 mmol/mmol catalyst/hour was observed using bismuth chromate at 250 °C. The formaldehyde produced through this method was selectively dehydrogenated to formate by an IrCl3 catalyst at room temperature under basic conditions, with a dehydrogenation rate of 20.1 mmol of hydrogen/mmole catalyst/hour. This completes a step-by-step and yet efficient cycle of formic acid dehydrogenation. Highlights: Single crystal X-ray structures of m- and o-BiOHCrO4 are reported for the first time. Higher catalytic conversion of formic acid to formaldehyde than previously shown. More active catalyst for formaldehyde dehydrogenation than observed previously.